A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae: Eurymelinae) - Wang, Xian-Yi; Wang, Jia-Jia; Dai, Ren-Huai (Zootaxa, 2021)
A new genus of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae: Eurymelinae) Longiaedeagus gen. nov. with type species Longiaedeagus flavofasciatus sp. nov. from China is described and illustrated. This new genus can be distinguished from other leafhopper genera by the broad style with truncate apex, and aedeagus with a long, unpaired retrorse preapical process.